2020
DOI: 10.21203/rs.3.rs-60143/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlation Between Glucose Metabolism Parameters Derived From FDG and Tumor TNM Stages and Metastasis-Associated Proteins in Colorectal Carcinoma Patients

Abstract: Background The aim of this study was to investigate the relationship between multiple metabolism parameters derived from FDG and tumor TNM stages as well as tumor metastasis-associated protein of GLUT-1 and MACC1 in colorectal carcinoma (CRC). Methods 38 patients (24 male and 14 female) with primary CRC confirmed by elective surgery pathological, who also underwent 18F-FDG PET/CT scans between 2017 and 2019 were included in this study. Tumor T, N and M classification according to the 7th American Joint Committ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…Under different SUVmax thresholds, SUVmax 30% and SUVmax 40% showed the same diagnostic e cacy, and the AUCs for predicting T3 from T4 were the same (0.748). The cutoff values were 8.803 and 8.758, and the cutoff value of FAPI was lower than that of FDG in a previous study [17]. However, because FAPI has a better target-background ratio, it can also achieve satisfactory visual effects, which is in accordance with the initial results obtained by Kömek et al [19].…”
Section: Relationship Between T Stage and Fapi Parameters In Crcsupporting
confidence: 88%
See 3 more Smart Citations
“…Under different SUVmax thresholds, SUVmax 30% and SUVmax 40% showed the same diagnostic e cacy, and the AUCs for predicting T3 from T4 were the same (0.748). The cutoff values were 8.803 and 8.758, and the cutoff value of FAPI was lower than that of FDG in a previous study [17]. However, because FAPI has a better target-background ratio, it can also achieve satisfactory visual effects, which is in accordance with the initial results obtained by Kömek et al [19].…”
Section: Relationship Between T Stage and Fapi Parameters In Crcsupporting
confidence: 88%
“…The T stage is a key factor in determining the optimal therapeutic plan in patients with CRC [4,24], such as surgery only, neoadjuvant chemoradiotherapy plus surgery, or de nitive chemoradiotherapy. Glucose metabolism parameters derived from FDG and tumor T stage have previously been reported [17]. Primary tumor lesions with higher SUVmax, TLG, and MTV values were prone to a high-T status.…”
Section: Relationship Between T Stage and Fapi Parameters In Crcmentioning
confidence: 87%
See 2 more Smart Citations
“…Since the discovery of MACC1, the authors of the present study, as well as several other research groups have demonstrated the clinical significance of MACC1 as a causal, prognostic and predictive biomarker for >20 solid cancer types (14), including meta-analyses for solid cancers, cancers of the digestive system, colorectal, hepatocellular, gastric, gynecological and breast cancer (17)(18)(19)(20)(21)(22). The causal contribution of MACC1 for rewiring cell metabolism has been demonstrated by the authors of the present study, as well as others (23)(24)(25). A recent study reported MACC1-driven metabolic networks in CRC, such as rewiring glucose and glutamine metabolism, an increase in glucose use by the enhanced surface of glucose transporter 1 (GLUT1) or an increase in glutamine and pyruvate use by enhanced uptake (25).…”
Section: Obesity Colorectal Cancer and Macc1 Expression: A Possible Novel Molecular Associationsupporting
confidence: 78%